2016
DOI: 10.1039/c5dt03438h
|View full text |Cite
|
Sign up to set email alerts
|

The flexibility of modified-linker MIL-53 materials

Abstract: The flexibility of eight aluminum hydroxo terephthalates [Al(OH)(BDC-X)]·n(guest) (BDC = 1,4-benzene-dicarboxylate; X = -H, -CH3, -Cl, -Br, -NH2, -NO2, -(OH)2, -CO2H) crystallising in the MIL-53-type structure was investigated upon thermal dehydration of as-made samples, superhydration and methanol adsorption/desorption using in situ powder X-ray diffraction (PXRD). Profile fitting was used to determine lattice parameters as a function of time and/or temperature to describe their structural evolution. It has t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…The powder XRD patterns show considerable peak broadening, suggesting either small crystallites or microstrain due to some inherent disorder in the structure (such as static disordered of ligand substituent positions), but this is typical for linkermodified MIL-53 materials for which full structure refinement has rarely been proved possible. 9 The incorporation of the intact ligand was confirmed by sulfur K-edge XANES spectroscopy, Figure ), 27 but this behaviour is similar to that seen in the other forms of MIL-53 with modified linkers, such as the case of dihydroxy-or bromo-, where a very small nitrogen uptake was ascribed to the bulky substituents. 6 Thus for the dithiolated material we conclude the material exists in a closed structure and presents a non-breathing framework.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The powder XRD patterns show considerable peak broadening, suggesting either small crystallites or microstrain due to some inherent disorder in the structure (such as static disordered of ligand substituent positions), but this is typical for linkermodified MIL-53 materials for which full structure refinement has rarely been proved possible. 9 The incorporation of the intact ligand was confirmed by sulfur K-edge XANES spectroscopy, Figure ), 27 but this behaviour is similar to that seen in the other forms of MIL-53 with modified linkers, such as the case of dihydroxy-or bromo-, where a very small nitrogen uptake was ascribed to the bulky substituents. 6 Thus for the dithiolated material we conclude the material exists in a closed structure and presents a non-breathing framework.…”
Section: Resultsmentioning
confidence: 71%
“…4 The potentially most versatile method of modification of MIL-53 materials, however, is the addition of functional groups to the aromatic ring of the terephthalate linker: this has been widely studied for a range of substituents and a common strategy is to premake substituted 1,4-benzenedicarboxylic acid that is then used as a reagent for the crystallisation of MIL-53. 5,6 This has been used with great effect to modify the response of the MIL-53 towards guest molecules and their thermally induced breathing behaviour, 7,8,9 or to introduce reactive functionalities that can be used for further chemical modification. 19 Others have shown that post-synthetic modification allows thiol groups to be added to a pre-made MOF: in the case of MIL-101(Cr) this allowed formation of an Hg 2+ adsorbent.…”
Section: Introductionmentioning
confidence: 99%
“…1a, all the peaks are consistent with those as reported in the previous references, where Al-MIL-53-NO 2 has a monoclinic crystal structure. 35,39,40 The main peak was located at ∼8.5°, which is ascribed to the (100) plane. 39 The crystals and morphologies were also characterized by scanning electron microscopy (SEM).…”
Section: Characterization Of Al-mil-53-nomentioning
confidence: 99%
“…26 The 3D framework of MIL-53 is built up of infinite chains of trans corner-sharing AlO 4 (µ-OH) 2 polyhedra, which are connected by 1,4-benzenedicarboxylate (BDC 2− ) molecules, to form onedimensional rhombic-shaped channels. 21,27,28 Bureekaew et al synthesised MIL-53 frameworks using 1,4-H 2 NDC and 1,4-H 2 BDC as linker molecules and subsequently impregnated the frameworks with HIm molecules. 26 The different steric influences of the linker molecules leads to different pore shapes and host-guest interactions, which was demonstrated via solid-state 2 H-NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%